Cooperative game scheduling and revenue sharing strategy for virtual power plants considering scenery uncertainty - SONG Duoyang; XUE Tianliang; LI Yipu; TU Jintong; BI Yuhao; WANG Mankang (电力工程技术, 2025)
Virtual power plants (VPP) efficiently aggregate small-capacity and large-volume distributed energy resources through advanced control technologies to participate in electricity market transactions. With the increase in the number of distributed energy sources, the volatility of their power output and the problem of their returns after aggregation still need to be solved. Based on this, a cooperative game scheduling model is proposed for multi-type distributed energy sources aggregated in a virtual power plant under the day-ahead power market. Firstly, the operation framework of multi-type distributed energy aggregation in virtual power plant is proposed. Then, a combined prediction model based on variational modal decomposition (VMD) and improved bidirectional multi gated long short-term memory (Bi-MGLSTM) network is established because the uncertainty of wind power output seriously affects the operation of the system. Secondly, the same type of distributed energy sources form alliances and aim to maximize the revenue from power sales, and construct a cooperative game scheduling model for multiple alliances of virtual power plants. In order to realize the fairness of revenue distribution among alliances and members, a multifactor improvement shapley value method and a two-stage refinement of the revenue distribution scheme based on the parity cycle kernel method are designed. Finally, the example results show that the proposed method effectively improves the prediction accuracy of wind power, realizes the cooperative and complementary operation among alliances within the virtual power plant, and ensures the fairness and reasonableness of the revenue distribution among multiple subjects.